**Answer:**

Thus # 2 is correct **(5 (y + 4))/2**

**Step-by-step explanation:**

Simplify the following:

(5 y (y^2 - 16))/(2 y (y - 4))

(5 y (y^2 - 16))/(2 y (y - 4)) = y/y×(5 (y^2 - 16))/(2 (y - 4)) = (5 (y^2 - 16))/(2 (y - 4)):

(5 (y^2 - 16))/(2 (y - 4))

y^2 - 16 = y^2 - 4^2:

(5 (y^2 - 4^2))/(2 (y - 4))

Factor the difference of two squares. y^2 - 4^2 = (y - 4) (y + 4):

(5 (y - 4) (y + 4))/(2 (y - 4))

Cancel terms. (5 (y - 4) (y + 4))/(2 (y - 4)) = (5 (y + 4))/2:

Answer: (5 (y + 4))/2